Enhancement of pool boiling characteristics by an addition of nano Aluminum oxide to R-141b over a rough horizontal steel circular heater. (February 2019) - Eid, Eldesouki I.; Khalaf-Allah, Reda A.; Tolan, Mohamed
Abstract: In this paper, an experimental investigation of the effect of addition of Aluminum oxide nano particles Al2 O3, to refrigerant, R-141b, on nucleate pool boiling heat transfer characteristics was carried out. The experiments were done over a flat steel horizontal circular heating surface, with different roughness, different nano particles concentration, different heat flux, and different normalized pressure. The roughness was varied at 0.14, 1.35, and 2.87 µm, the concentrations were 0.001, 0.005, 0.01, 0.03, 0.05 and 0.1% by Vol., The applied heat flux was varied up to 150 kW/m 2 and the operating normalized pressure was varied at 0.01, 0.125, and 0.3. The results show that; the heat transfer coefficient increases with the concentration up to 0.05%. However, at high concentration up to 0.1%, the heat transfer coefficient decreases due to the accumulation of deposits of nanoparticles above the heating surface. The enhancement in heat transfer coefficient ranged from 24% to 60% for the normalized pressure from 0.01 to 0.3 at the same heat flux and concentration. At a heat flux of 150 kW/m 2, 0.3 normalized pressure and a roughness of 2.87 µm, and a concentration of 0.05%, the enhancement reaches to 124%. An empirical correlation was deduced to formulate the relation among heat transfer coefficient, heat flux, pressure, concentration, and roughness within a maximum deviation of about ±9%.